Analisa Peraturan Pemotongan Pajak Penghasilan Berdasarkan Undang-Undang Nomor 7 Tahun 2021 - Praditya, Zonehara Bima; Prawesthi, Wahyu (BUDGETING : Journal of Business, Management and Accounting, 2023)
This journal aims to conduct an in-depth analysis of the income tax withholding regulations based on this law. The research method used is a comprehensive descriptive analysis, by collecting data from various sources such as laws and regulations, tax guidelines, and related literature studies. The author identifies and analyzes significant changes in the income tax withholding regulations stipulated in Law Number 7 of 2021. The results of the analysis show that Law Number 7 of 2021 brings substantial changes in the procedure for withholding income tax. Several changes include adjustments to withholding rates, criteria for tax subjects that must be withheld, and the introduction of a withholding mechanism for certain special transactions. This research makes a significant contribution to the understanding of income tax withholding regulations in Indonesia, especially after the enactment of Law Number 7 of 2021. The results of the analysis and findings in this journal are expected to be a reference for tax practitioners, academics, and other related parties to optimize compliance and fulfillment of tax obligations by following the applicable regulations. In addition, it is hoped that it will also serve as a guide for policy makers in formulating better and more efficient tax policies in the future. Keywords: Income, Regulation, Tax, Withholding.